MARKET OVERREACTION PADA IDX 30 (PERIODE PENELITIAN 2016-2019) - Satria, I Gusti Agung Egitha; Yadnya, I Putu (E-Jurnal Manajemen; Vol 10 No 8 (2021)DO - 10.24843/EJMUNUD.2021.v10.i08.p03, 2021)
The availability of relevant information on a capital market, especially on traded securities, is very important for investors, so that the capital market can be said to be efficient. Investor characteristics can result in Stock Price movements. Investors who are irrational in investing can cause real overreaction. This study aims to analyze the existence of market overreaction on IDX 30 for the 2016-2019 study period. Sampling in this study using purposive sampling technique and got a sample of 17 from 45 population companies listed on the IDX 30 index for 8 semesters. This study uses abnormal returns winner, loser, and loser-winner as research variables. The statistical test used one sample t-test to test for differences in the Average Cumulative Abnormal return of winners, losers, and loser-winners. The results of this study indicate that the occurrence of market overreaction on winner, loser, and ACAR loser-winner portfolios is indicated by the Price Reversal for each ACAR, but the one sample t-test significance test shows that the market overreaction that occurs is not significant. indicated by t-count <t-table. Keywords : Market overreaction , Market Efficiency, Price Reversal , Winner - Loser Anomaly